Research on the evolution of physical teachers and physical teaching policy: A perspective from China - Mingliang Xiong; Bin Yan; Ruilin Xu; Fang Liu; Cuixiang Dong (PLoS ONE, 2026)
This study aims to comprehensively and profoundly explore the history of changes in China’s physical teachers and physical teaching policies. Focusing on policies related to physical teachers and teaching published between 1950 and 2023, we employed text mining and topic-matching techniques to construct an algorithmic model for analyzing physical teachers and teaching policy topic types and attitude orientations, thereby capturing the internal logic and external characteristics of the policy texts. Through a sub-period analysis, we examined the evolution of physical teachers and teaching policy themes and attitudes across different historical periods. The key findings reveal that policy themes have gradually exhibited a trend of diversification and refinement: initially emphasizing the training of physical teachers’ basic qualities, they shifted to highlighting the promotion of professional skills, and later advocated the development of comprehensive quality and innovative abilities. Concurrently, policy attitudes have transformed from being unitary to pluralistic and from rigid to flexible, with an increasing focus on guidance and encouragement. Additionally, the process of policy change demonstrates continuity and inheritance, which ensures the stability and coherence of the policy system.